Akuntabilitas Penggunaan Dana Belanja Tidak Terduga Pada Badan Keuangan dan Aset Daerah Kabupaten Sidenreng Rappang - J. Jumiati; Muhammad Nur; Muhammad Rais (Public Inspiration : Jurnal Administrasi Publik, 2025)
This study aims to analyze the accountability of the use of the Emergency Budget (BTT) funds in the Financial and Asset Management Agency of Sidenreng Rappang Regency. The Emergency Budget is an allocated fund for unforeseen urgent needs, such as natural disasters and other emergencies. This research employs a qualitative descriptive approach to understand the mechanisms of disbursement, oversight, and accountability of BTT funds. Data were collected through in-depth interviews, observations, and document reviews involving relevant stakeholders, including regional financial officers and budget users. The findings reveal that while the BTT fund management mechanism adheres to legal frameworks such as Government Regulation No. 12 of 2019 and Law No. 24 of 2007, its implementation faces several challenges. The main issues include bureaucratic delays and limited human resources, which hinder the timely disbursement of funds for disaster response. Monitoring and accountability processes are conducted through transparent financial reporting and periodic audits following governmental accounting standards. This study recommends improving BTT fund governance by enhancing human resource capacity, streamlining bureaucratic processes, and optimizing information technology. These measures are expected to ensure the more effective, efficient, and accountable management of emergency funds, thereby increasing public trust in the government.